The Beckoning Void in Moravagine - Stephen K. Bellstrom (Studies in 20th & 21st Century Literature, 1979)
The Chapter «Mascha,» lying at the heart of Cendrars's Moravagine, contains within it a variety of images and themes suggestive of emptiness. The philosophy of nihilism is exemplified in the motivations and actions of the group of terrorists seeking to plunge Russia into revolutionary chaos. Mascha's anatomical orifice, symbolizing both a biological and a psychological fault, and the abortion of her child, paralleled by the abortion of the revolutionary ideal among her comrades, are also emblematic of the chapter's central void. Moreover, Cendrars builds the theme of hollowness by describing Moravagine with images of omission, such as «empan» (space or span), «absent,» and «étranger.» Moravagine's presence, in fact, characteristically causes an undercurrent of doubt and uncertainty about the nature of reality to become overt. It is this parodoxical presence which seems to cause the narrator (and consequently the narrative) to «lose» a day at the most critical moment of the story. By plunging the reader into the narrator's lapsus memoriae, Cendrars aims at creating a feeling of the kind of mental and cosmic disorder for which Moravagine is the strategist and apologist. This technique of insufficiency is an active technique, even though it relies on the passive idea of removing explanation and connecting details. The reader is invited, or lured, into the central void of the novel and, faced with unresolvable dilemmas, becomes involved in the same disorder that was initially produced.
Keywords: Blaise Cendrars; Moravagine; Mascha; emptiness; nihilism; uncertainty; doubt